Air- and oxygen-blown characterization of coal and biomass by thermogravimetric analysis. (15th January 2018) - Mureddu, Mauro; Dessì, Federica; Orsini, Alessandro; Ferrara, Francesca; Pettinau, Alberto
Graphical abstract: Highlights: Coal and biomass samples have been experimentally characterized by TGA and DSC. Combustion and oxy-combustion behaviours are assessed and kinetically analysed. Kinetic analysis is based on both FWO and KAS methods and results are compared. Oxy-combustion can improve the burning rate of fuels, shortening the burning time. Both FWO and KAS are reliable for combustion, but only for coal for oxy-combustion. Abstract: This paper reports on the results of air-blown combustion and oxy-combustion kinetic characterization (comparing two different isoconversional methods: Flynn-Wall-Ozawa and Kissinger-Akahira-Sunose) of different kinds of coal (from Italy, South Africa and Hungary) and biomass (pine and eucalyptus chips) by thermogravimetric analysis (TGA) and differential scanning calorimeter (DSC) together with the assessment of different characteristic combustion parameters. It can be observed that the burning rate of fuels can be improved by the oxy-combustion process, shortening the burning time (a mean reduction of the burnout time of 14% and 22% can be observed for coal and biomass samples, respectively). Moreover, biomass shows better ignition performance than coal and enhances combustibility indexes ( S and Hf ), especially in oxy-combustion conditions. For example, the S index, which reflects combustion properties, increases by an order of magnitude for biomass combustion and oxy-combustion with respect to coal values, thus indicating a higher combustion activity for biomass; an opposite trend can be observed for the Hf index, which describes the rate and intensity of the process and is lower for biomass than for coal, thus indicating better performance for wood chips combustion. Kinetic analysis shows that the activation energy Ea varies with conversion values, reflecting the kinetic complexity in both the processes. Moreover, with the same range of heating rates (10 ≤  β  ≤ 50 °C/min) and for the overall range of conversion (0.1 ≤  α  ≤ 0.9), both of the models used fit the experimental data in combustion regime, whereas the increase of the oxygen concentration makes the results reliable for coal samples and more sensitive to weight loss for biomass samples.